Peningkatan Hasil Belajar Seni Grafis Melalui Metode Demonstrasi Bagi Siswa Kelas IX SMP Negeri 9 Bolaang Mongondow Utara - Adam, Sri Nuryulistiani; Sudana, I Wayan; Dangkua, Suleman (Innovative: Journal Of Social Science Research, 2025)
The research aims to improve student learning outcomes in Graphic Arts subjects through demonstration learning methods. The research uses classroom action methods. Data were collected through observation, tests, and literature studies. Data analysis used the percentage of individual and classical learning completion. The results showed that after using the demonstration method, there was an increase in student learning outcomes in graphic arts subjects in the aspects of expression and appreciation. The increase in the expression aspect in cycle I reached 12.5%, from 50% to 62.50% and an increase in the appreciation aspect of 12.5%, from 50% to 62.5%. Although there was a significant increase, it had not yet reached the minimum learning completion set, which was ≥75%. Therefore, cycle II was carried out with several improvements from the shortcomings of cycle I. In cycle II, there was an increase in learning outcomes in the expression aspect of 20.83%, from 62.50% to 83.33%, and in the appreciation aspect of 29.16%, from 62.50% to 91.66%. It is concluded that the application of demonstration learning methods can improve student learning outcomes.